Short Communication: The higher laccase enzyme producer, Cerrena sp. BMd.TA.1, isolated from Gunung Rinjani National Park, West Nusa Tenggara, Indonesia - SARAH ASIH FAULINA; ASEP HIDAYAT; SYAMSUL FALAH; Apri Heri Iswanto (Society for Indonesian Biodiversity, 2020)
Abstract. Faulina SA, Irfani M, Falah S, Hidayat A, Iswanto AH. 2020. Short Communication: The higher laccase enzyme producer, Cerrena sp. BMd. TA.1, isolated from Gunung Rinjani National Park, West Nusa Tenggara, Indonesia. Biodiversitas 21: 3837-3842. Lies in the Wallace line, Gunung Rinjani National Park (GRNP) offers unique biodiversity, fungi included. Fungal enzymes have been unceasingly searched and studied for various applications, particularly for biodegradation. Fungal laccase enzyme showed prospective environmental-friendly approach in treating industrial effluent, remazol brilliant blue R (RBBR) which is used as a synthetic dye. This study aimed to explore the laccase-producing fungi from the GNRP, as well as investigate their ability in decolorizing RBBR. The study discovered that the most prospective fungi isolate, molecularly identified as Cerrena sp. BMd.TA.1, produced a high level of laccase (> 2300 U mL-1) and manganese peroxidase (MnP, 300 U mL-1). In the application of this isolate, the laccase showed as predominant enzyme in RBBR decolorization process and the RBBR could be decolorized more than 80% at 24 h reaction. It suggested that Cerrena sp BMd.TA.1 isolate is highly potential as laccase enzyme producer and may be considered for further investigations in its applications for biodegradation, especially of dyes effluent.